SYSTEMS OF SOFT SQUEEZING IN THE MACHINES OF CONTINUOUS CASTING AND THEIR INFLUENCE ON THE SLUGS MACROSTRUCTURE QUALITY - V. A. Matochkin; S. V. Terletskij; V. E. Marushkevich (Литьë и металлургия, 2010)
The application of the systems of dynamic soft squeezing on machines of continuous casting is justified as the way of solving of the microstructure quality problem.